The Controversy About the Effects of Different Doses of Corticosteroid Treatment on Clinical Outcomes for Acute Respiratory Distress Syndrome Patients: An Observational Study - Yang, Jia-Wei; Jiang, Ping; Wang, Wen-Wen; Wen, Zong-Mei; Mao, Bei; Lu, Hai-Wen; Zhang, Li; Song, Yuan-Lin; Xu, Jin-Fu (Frontiers in Pharmacology, 2021)
Background: Corticosteroid usage in acute respiratory distress syndrome (ARDS) remains controversial. We sought to explore the correlation among the different doses of corticosteroid administration and the prognosis of ARDS. Methods: All patients were diagnosed with ARDS on initial hospital admission and received systemic corticosteroid treatment for ARDS. The main outcomes were effects of corticosteroid treatment on clinical parameters and the mortality of ARDS patients. Secondary outcomes were factors associated with the mortality of ARDS patients. Results: 105 ARDS patients were included in this study. Corticosteroids treatment markedly decreased serum interleukin-18 (IL-18) level (424.0±32.19 vs 290.2±17.14; p=0.0003) and improved arterial partial pressure of oxygen/ fraction of inspired oxygen (PaO2/FiO2) (174.10±65.28 vs 255.42±92.49; p<0.0001). The acute physiology and chronic health evaluation (APACHE II) score (16.15±4.41 vs 14.88±4.57, p=0.042) decreased significantly on the seventh day after systemic corticosteroid treatment. Interestingly, the serum IL-18 decreased significantly (304.52±286.00 vs 85.85±97.22, p<0.0001), while the improvement of PaO2/FiO2 (24.78±35.03 vs 97.17±44.82, p<0.001) was inconspicuous after systemic corticosteroid treatment for non-survival patients, compared with survival patients. Further, the receiver operating characteristic (ROC) model revealed, when equivalent to methylprednisolone usage was 146.5mg/d, it had the best sensitivity and specificity to predict the death of ARDS. Survival analysis by Kaplan-Meier curves presented the higher 45-day mortality in high-dose corticosteroid treatment group (Long-Rank test p<0.0001). Multivariate Cox regression analyses demonstrated that serum IL-18 level, APACHE II score, D-Dimer and high-dose corticosteroid treatment were associated with the death of ARDS. Conclusions: Appropriate dose of corticosteroids may be beneficial for ARDS patients through improving the oxygenation and moderately inhibiting inflammatory response. The benefits and risks should be carefully weighed when using high dose corticosteroid for ARDS.